A Study of Double Glass Covered Trapezoidal Salt Gradient Solar Pond Coupled with Reflector - Kumar, Sandeep (My University, 2016)
In this study, a trapezoidal salt gradient solar pond (TSGSP) having a top surface area of m2 and bottom surface area of m2 and depth of 0.90 m has been constructed to investigate the temperature distribution and thermal performance of TSGSP. The top surface of solar pond is covered with double glass cover in order to reduce the evaporative and convective losses from the top. A reflector made of aluminium sheet is used for enhancing the solar intensity on the top surface of the solar pond during sunny hours. The position of reflector is changed manually in steps to track the sun in order to receive maximum beam radiation on the reflector surface. This reflector is also used as a cover on the top surface of the solar pond to reduce the thermal losses during the night. The sunny area ratio of trapezoidal solar pond is calculated theoretically and compared with that of square solar pond. For the purpose of comparison of sunny area ratio between trapezoidal and square solar ponds, three cases of square solar ponds are considered in this study. These three cases of square solar ponds are: square solar ponds with the same surface area and volume, with the same surface area and height and with the same height and volume as that of trapezoidal solar pond. The experimental results show that the average temperature of solar pond without double glass cover is 44.2 °C and this temperature increased to 55°C when solar pond is covered with double glass cover. The use of reflector with fixed position and with changing position enhances the average solar intensity on the top surface of solar pond by 22% and 47%, respectively. The thermal efficiencies of LCZ, NCZ and UCZ for the trapezoidal solar pond with double glass cover and reflector are estimated to be 32.73%, 23.22% and 5.30%, respectively. The results of theoretical analysis provide an information that the trapezoidal solar pond and the square solar ponds with the same surface area and volume, with the same surface area and height and with the same height and volume as that of trapezoidal solar pond have highest sunny area ratio of 94.12%, 88.86%, 84.2% and 78.6% respectively in the month of June, 2016.
Master of Technology-Thermal Engineering
Keywords: Trapezoidal solar pond; Glass cover; Reflector cover; Shading areas; Temperature distribution